UJI TOKSISITAS TERATOGENIK EKSTRAK ETANOL DAUN ASAM JAWA (Tamarindus indica Linn) TERHADAP TIKUS (Rattus norvegicus) - Rahimah, Sitti; Salampe, Mirnawati; Rahmania, Nurbaiti (Jurnal Ilmiah As-Syifaa, 2020)
In this study of teratogenic toxicity tests was carried out on the ethanol extract of tamarindus leaves (Tamarindus Indica Linn) on rats (Rattus norvegicus) during the organogenesis period. This study aims to know the safety and toxicity of the administration of ethanol extract of tamarind leaves (Tamarindus indica L.) to fetus rats (Rattus norvegicus) with macroscopic parameters including number, resorption, weight, and skeleton of the fetus. 15 animals were divided into 3 groups, each group consisted of 5 rats. Group I was treated with 0.5% Na CMC as normal control, Â group II was treated with ethanol extract of tamarind leaves with a dose of 14 mg / 200 g BW for 10 days and group III was given a simvastatin tab at a dose of 10 mg / kg BW. Treatment was given orally during the organogenesis period on the 5th to 15th day of pregnancy. On the 16th day, laparatomy of the rat and fetus was removed from the uterus. The results showed that the suspension of ethanolic extract of tamarind leaves did not cause teratogenic occurrence in fetal rats, and the control of simvastatin caused teratogenic due to resorption, less fetal weight, hand and foot defect, and death in the fetus, compared to the normal control group.